2019
DOI: 10.1021/acs.jafc.8b06047
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-Guided Analysis of Key Taste-Active Compounds in Pufferfish (Takifugu obscurus)

Abstract: To investigate key taste-active components in Takifugu obscurus (T. obscurus), twenty-eight putative taste compounds in cooked muscle of T. obscurus were quantitatively analyzed and the pivotal components were identified by taste reconstitution, omission and addition tests. Moreover, the role of flavor peptides in overall taste profile of T. obscurus were evaluated. Sensory evaluation revealed that glutamic acid, serine, proline, arginine, lysine, adenosine-5´-monophosphate, inosine-5´-monophosphate (IMP), suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…There were 4 eight-peptide and 1 six-peptide. Liu et al [31] identified seven-peptide (Pro-Val-Ala-Arg-Met-Cys-Arg) and eight-peptide (Tyr-Gly-Gly-Thr-Pro-Pro-Phe-Val) in Takifugu obscurus (T. obscurus). The two peptides were the key substances on the taste of pufferfish flavor.…”
Section: Identification Of Taste Peptides By Lc-q-tof-msmentioning
confidence: 99%
“…There were 4 eight-peptide and 1 six-peptide. Liu et al [31] identified seven-peptide (Pro-Val-Ala-Arg-Met-Cys-Arg) and eight-peptide (Tyr-Gly-Gly-Thr-Pro-Pro-Phe-Val) in Takifugu obscurus (T. obscurus). The two peptides were the key substances on the taste of pufferfish flavor.…”
Section: Identification Of Taste Peptides By Lc-q-tof-msmentioning
confidence: 99%
“…7 Umami compounds generally include inosinic acid, glutamic acid, ornithine and many umami peptides. [7][8][9][10][11][12] In recent years, increasing attention has been paid to umami peptides. 13 Marine food has a strong umami taste and can be used as an important raw material in the preparation of umami peptides.…”
Section: Introductionmentioning
confidence: 99%
“…A primary focus of pufferfish research is the identification of the compounds contributing to its favourable umami and kokumi taste characteristics. Free amino acids, nucleotides, organic acids and bases, inorganic ions, and peptides have been identified as key substances imbuing pufferfish with its typical umami taste 4,6,7 . The key odorants involved in the aroma of cooked pufferfish have been identified as trimethylamine, octanal, ( E )‐2‐octenal, 1‐octen‐3‐ol, 2‐ethyl‐1‐hexanethiol, ( E , E )‐2,4‐octadienal, 2‐acetylthiazole and 2‐acetylpyrrole 8 .…”
Section: Introductionmentioning
confidence: 99%